Sistem Informasi Akuntansi Pengelolaan Kas Berbasis Dekstop di Masjid Pusdai Jawa Barat - Novita Andini (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
In recording cash, mosques are still based on semi-computers so it can result in inaccurate financial statements due to errors in data input, besides that storing archives or documents manually has many risks such as lost or damaged documents. This study aims to design a computerized cash management system so that all inputted data is stored in a database making data storage and management more efficient, and reporting can be done automatically and accurately. In designing a cash management accounting information system the author uses the waterfall development method starting with system analysis, system design, implementation, testing, and maintenance. The tools used in this design are Microsoft Visual Studio 2010 and Microsoft Access as databases. This research produces a system that can manage cash receipts and cash disbursements accurately and store transaction evidence into a database and make it easier to make reports.